The effectiveness of Grade 3 teachers’ implementation of poetry through play pedagogies - Charity Z. Fynn; Blanche Ndlovu (South African Journal of Childhood Education, 2024)
Background: Poetry predates all other genres of literature, and it has been argued that the relationship between poetry and language is inextricable. The ability of African people to articulate their own stories was largely silenced by colonialism. Poems and lyrics have been known to create a bridge between individuals in meaningful words and songs.